Detection of TNF Alpha Level as Biomarker in Different Stages of Cutaneous Leishmaniasis Infection - Hussein, Ashjan Mohammed; Ali, Hayder Zuhair (Iraqi Journal of Science, 2022)
Leishmaniasis is a global illness that is endemic in many countries, including Iraq. The characteristic of cutaneous leishmaniasis (CL) is the development of skin ulcers that are controlled by the immune system. Tumor necrosis factor-alpha (TNF-α), a cytokine generated by the innate immune response to CL infection, can influence disease clearance in the human host. The effect of this pro-inflammatory cytokine in CL ulcer development during the infection is not well established. In this study TNF-α level was detected in the patients who suffered from cutaneous leishmaniasis. This level was also assessed in the newly diagnosed patients and others who were undergoing different stages of pentostam treatment. Notably the results revealed a significant increment in TNF-α serum levels in the test groups of newly infected patients, as well as, in the patients enduring second and third trials of pentostam treatment, which was (1125.49, 838.75, 1264.26) ng/ml accordingly, in comparison with healthy control group  which was 235.35 ng/ml. Furthermore, there was no significant observation in TNF-α among the three patient groups. The perceived rise of TNF-α serum levels may give insights into this pro-inflammatory cytokine as a biomarker in the prognosis and tracking the disease progression.